Restoration of grazing land to increase biomass production and improve soil properties in the Blue Nile Basin: effects of infiltration trenches and Chloris gayana reseeding - Erkossa, Teklu; Geleti, D.; Williams, Timothy O.; Laekemariam, F.; Haileslassie, Amare (Cambridge University Press, 2022)
Degradation of crop and grazing lands is a pervasive problem that negatively impacts agricultural productivity and livelihoods of crop-livestock farmers in the Blue Nile basin of Ethiopia. Area enclosure together with a cut and carry livestock feeding system is often advocated as an approach for the regeneration of degraded grazing lands. This paper reports the results of a two-year farmer participatory study conducted to assess the effects of infiltration trenches (ITs) and Chloris gayana Kunth (Rhodes grass; cultivar Masaba; tetraploid; C4 grass species) reseeding on restoration of degraded grazing lands. A split plot design was used with IT as the main plot and C. gayana reseeding as a sub-plot on 28 private grazing plots under enclosure. The results showed that IT alone increased soil moisture content and prolonged the growing period. IT and C. gayana reseeding together significantly (P = 0.05) increased herbage dry matter yield and improved soil chemical properties. The highest mean herbage dry matter yield (21 Mg ha-1 per cut) was recorded for plots treated with IT and reseeded with C. gayana. The higher herbage dry matter yield was attributed to increased soil moisture and the resultant prolonged growing period induced by the trenches coupled with the ability of C. gayana to effectively utilize the retained water. The results suggest that an integrated land management approach involving enclosure, in-situ water conservation and C. gayana reseeding can rapidly increase biomass productivity on degraded grazing lands while also enhancing soil quality with concomitant livelihood benefits for farmers.